2020
DOI: 10.2217/fon-2020-0928
|View full text |Cite
|
Sign up to set email alerts
|

Truscreen Detection of Cervical Tissues for High-Risk Human Papillomavirus-Infected Women During the COVID-19 Pandemic

Abstract: Objectives: To evaluate the efficacy of TruScreen (TS01) for high-risk human papillomavirus (HR-HPV) women compared with other methods in reducing colposcopy referral rates in hospitals. Methods: A single-center, prospective, case–control study was conducted from December 2019 to June 2020. Results: Among 139 (46.2%) HR-HPV positive patients, 58 were CIN1, 52 were CIN2-3 and 29 had cervical cancer (n = 29). The sensitivity and specificity of detecting CIN2+ by TS01, colposcopy and HPV16/18 testing were 96.3% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…A recent study about TS applied in hrHPV infected women reported TS combined with HPV 16/18 had the highest specificity (83.6%) comparing with TS alone or HPV 16/18 alone [18]. Our study reported similar specificities of TS combined with hrHPV of significancy (82.8% for CIN1+, 73.3% for CIN2+) and significantly higher PPV of CIN1+ comparing with hrHPV alone.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A recent study about TS applied in hrHPV infected women reported TS combined with HPV 16/18 had the highest specificity (83.6%) comparing with TS alone or HPV 16/18 alone [18]. Our study reported similar specificities of TS combined with hrHPV of significancy (82.8% for CIN1+, 73.3% for CIN2+) and significantly higher PPV of CIN1+ comparing with hrHPV alone.…”
Section: Discussionsupporting
confidence: 78%
“…We used Hologic Aptima HPV test for testing 14 types hrHPV E6/E7 mRNA (types 16,18,31,33,35,39,45,51,52,56,58,59,66,68) and Hybribio Rapid GenoArray to determine the 21 specific HPV types including 13 high-risk types (types 16,18,31,33,35,39,45,51,52,56,58,59, and 68), 6 low-risk types (types 6,11,42,43,44,and CP8304 [81]) and 2 probable high-risk types (types 53 and 66). The tests were carried out and reported according to manufacturer's instructions.…”
Section: Hpv Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a shift to minimally invasive surgery (laparoscopy or robotic surgery) when possible is recommended 6,16,27,28 , as it is associated with shortened recovery and hospitalization periods and thus minimizing the risk for a perioperative COVID-19 infection. Alternatives to the standard cytology screening 29 , new fractionation systematics 30 and the question of novel care and multidisciplinary communicative models have also been risen during this pandemic 7,18,20 . During the pandemic, decrease in minimally invasive surgery were reported by less-experienced gynaecologic oncologists 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a shift to minimally invasive surgery (laparoscopy or robotic surgery) when possible is recommended [ 6 , 16 , 27 , 28 ], as it is associated with shortened recovery and hospitalisation periods and thus minimising the risk for a perioperative COVID-19 infection. Alternatives to the standard cytology screening [ 29 ], new fractionation systematics [ 30 ] and the question of novel care and multidisciplinary communicative models have also been risen during this pandemic [ 7 , 18 , 20 ]. During the pandemic, decrease in minimally invasive surgery was reported by less-experienced gynaecologic oncologists [ 31 ].…”
Section: Discussionmentioning
confidence: 99%